Clinical and Economic Burden of Valley Fever in Arizona: An Incidence-Based Cost-of-Illness Analysis. (28th December 2020) - Grizzle, Amy J; Wilson, Leslie; Nix, David E; Galgiani, John N
Abstract: Background: Coccidioidomycosis, ie, Valley fever, is an important fungal infection in the Southwest, with half to two thirds of all cases occurring in Arizona. This endemic respiratory disease can range from primary uncomplicated pneumonia to disseminated infection such as meningitis with chronic pulmonary complications. Valley fever diagnoses have risen over recent years and cause substantial morbidity and economic burden in Arizona. Methods: We estimated the lifetime cost-of-illness associated with all cases of Valley fever diagnosed in 2019 in Arizona. Natural history of the disease was determined from literature and expert opinion and assigned costs from national data sources to determine lifetime direct and indirect costs (work loss). Results: Total lifetime costs of $736 million were estimated for the 10 359 cases of Valley fever diagnosed in Arizona in 2019. Direct costs of $671 million accounted for over 90% of expenditures, with $65 million in indirect costs. Disseminated infection produces the highest economic burden at $1.26 million direct and $137 400 indirect costs per person. The lowest Valley fever lifetime costs were for cases of primary uncomplicated pneumonia with $23 200 in direct costs and $1300 in lost wages. The average lifetime direct costs across all Valley fever manifestations are $64 800 per person diagnosed in Arizona in 2019 and $6300 for indirect costs. Conclusions: Valley fever is responsible for substantial economic burden in Arizona. Our estimates underscore the value of supporting research into developing more rapid diagnostic tests, better therapies, and ultimately a preventative vaccine to address this important public health problem in Arizona. Abstract : Valley fever is an important disease in Arizona causing substantial morbidity and cost. We estimated lifetime costs for newly diagnosed cases of Valley fever in Arizona in 2019 at $671 million in direct costs and $65 million in indirect costs.